Behavioral and electrophysiological responses of fall armyworm larval parasitoid Coccygidium luteum to maize and companion plant volatiles - Emmanuel Peter; Sevgan Subramanian; Abdullahi Yusuf; Samira A. Mohamed; Baldwyn Torto; Emily A. Martin; Amanuel Tamiru (BioControl, 2026)
Companion cropping and biological control are among the best agronomic practices recommended for ecologically sustainable management of the invasive fall armyworm (FAW), Spodoptera frugiperda J.E. Smith (Lepidoptera: Noctuidae). Companion plants may suppress the FAW population by repelling the pest, disrupting host-plant location and recruiting biocontrol agents such as parasitoids. These interactions are primarily mediated by plant-derived volatile organic compounds (VOCs). Understanding parasitoids’ responses to VOCs emitted by companion plants enables selection of suitable cultivars to enhance biological control and design appropriate intercropping systems for effective FAW management. This study investigated behavioral and electrophysiological responses of a key FAW larval parasitoid, Coccygidium luteum Brullé (Hymenoptera: Braconidae), to odors from maize and different companion crops used in maize-based intercropping systems. In an olfactometer bioassay, gravid C. luteum were attracted to volatiles from FAW-damaged maize and intact companion plants (sweet potato, beans, groundnut) compared to control, but not to intact maize or cassava. Interestingly, females of C. luteum were equally attracted to volatiles from intact companion plants and FAW-damaged maize in multiple-treatment assays, suggesting that certain VOCs emitted by both plants may have ecological relevance. Chemical and electrophysiological analyses identified several bioactive compounds in the companion plant volatiles, including ( E )-2-hexenal, (Z)-3-hexenyl acetate, nonanal, ( E )-β-ocimene, ( E )-4,8-dimethyl-1,3,7-nonatriene, decanal, ( E )-nerolidol, and ( E , E )-4,8,12-trimethyl-1,3,7,11-tridecatetraene, known to influence parasitoid foraging. These findings provide further insight into the companion plants-FAW-parasitoid interactions and support the development of effective, economical, and environmentally friendly FAW management strategies using companion cropping and biological control.